Cell-Mediated Immunogenicity of Influenza Vaccination in Patients With Cancer Receiving Immune Checkpoint Inhibitors. (1st June 2020) - Kang, Chang Kyung; Kim, Hang-Rae; Song, Kyoung-Ho; Keam, Bhumsuk; Choi, Seong Jin; Choe, Pyoeng Gyun; Kim, Eu Suk; Kim, Nam Joong; Kim, Yu Jung; Park, Wan Beom; Kim, Hong Bin; Oh, Myoung-don
Abstract: Background: We assessed cell-mediated immune (CMI) responses of influenza vaccination in patients with cancer receiving immune checkpoint inhibitors (ICIs), which remain elusive. Methods: Vaccine-elicited CMI responses in patients receiving ICIs or cytotoxic agents were investigated by flow cytometry. Polyfunctional cells were defined as T cells that express 2 or more of interleukin 2 (IL-2), interleukin 4 (IL-4), interferon gamma (IFN-γ), and CD107a. An adequate CMI response was defined as an increase of polyfunctional T cells against both H1N1 and H3N2 strains. Results: When comparing ICI (n = 11) and cytotoxic chemotherapy (n = 29) groups, H1N1-specific IL-4 or IFN-γ–expressing CD4 + T cells, IL-2, IL-4, IFN-γ, or CD107a-expressing CD8 + T cells, H3N2-specific IFN-γ–expressing CD4 + T cells, and CD107a-expressing CD8 + T cells were more frequent in the ICI group. Fold changes in polyfunctional H3N2-specific CD4 + (median, 156.0 vs 95.7; P  = .005) and CD8 + (155.0 vs 103.4; P  = .044) T cells were greater in the ICI group. ICI administration was strongly associated with an adequate CMI response for both CD4 + and CD8 + T cells ( P =  .003). Conclusions: CMI responses following influenza vaccination were stronger in the ICI group than in the cytotoxic chemotherapy group. Influenza vaccination should be strongly recommended in patients with cancer receiving ICIs. Abstract : Flow cytometric analyses revealed that patients with cancer receiving immune checkpoint inhibitors (ICIs) had higher influenza-specific vaccine-elicited cell-mediated immune responses compared with those receiving cytotoxic chemotherapy after seasonal influenza vaccination, which supports annual influenza vaccination in ICI-treated patients.